Respostas

2014-06-19T09:28:58-03:00
Fazer PASSO A PASSO

4)
a) 5² : (5+1-1) + 4x2 =
 5x5  :   (5+0)  +   8  =
  25  :      5      +   8  =
        5             + 8    =       13

b) (3+1)² + 2x5 - 10º =     (qualquer número elevado a ZERO = 1)
      (4)²    +  10 -  1  =
  4x4        +      9      =
   16        +       9      =  25



c) 3² :(4-1) + 3x2² =
3x3 : (3)   + 3x(2x2) =
 9    : 3     +  3x4 =
      3         +   12   =  15


d) 70 - [ 5x  (2² :4) +   3³]
    70 - [ 5x(2x2:4) + 3x3 ]=
    70 - [5x(  4 : 4)  +  9   ]=
    70 -[5  x   1        + 9] =
    70 - [     5           + 9 ]=
    70 - [      14]=
    70-14 = 56
 
 
 e) (7+4) x (3² -2³ )=
     (11)   x(3x3 - 2x2x2)=
     (11) x  ( 9   -    8     ) =
      11  x        1      =   11

f) 5² + 2³ -     2x(3+9)=
5x5  +2x2x2- 2x(12) =
 25   +   8    - 24 =
      33         -= 24 =   9


g) 6² : 3² + 4x10 - 12 =
6x6 : 3x3 + 4x10 - 12 =
 36  :  9   +  40    - 12 =
      4       +  40   -  12 =
             44         -  12 =  32

h) (7² - 1) : 3 + 2x5 =
(7x7   - 1) : 3 +  10 =
( 49   - 1) : 3  + 10 =
      48      : 3  + 10 =
             16     + 10 =  26
 

5)

a) 5 + 4² - 1 =
    5 + 4x4 - 1 =
    5 +  16 - 1 =
        21    - 1 =  20

b)      3⁴ - 6 + 2³ =
3x3x3x3  -6 + 2x2x2 =
       81 -  6 +    8      =
       81 + 8 - 6 =
          89 - 6 = 83

c)         2⁵ - 3² + 1⁹  =    (1 elevado a QUALQUER POTENCIA(positiva) = 1)
2x2x2x2x2 - 3x3 + 1⁹=
           32  - 9     + 1 =
           32 + 1 - 9 =
             33    - 9 =  24

d) 10² - 3² + 5 =
10x10 - 3x3 + 5 =
   100  - 9    + 5 =
    100 + 5 - 9 =
       105 - 9 =  96

e)  11² - 3² + 5 =
 11x11 - 3x3 + 5 =
    121  - 9    + 5 =
    121+ 5 - 9 =
    126 - 9 =  117


f) 5x3² x 4=
 5x(3x3) x  4=
5x   9     x  4 =
  45        x 4 =
45x4= 180

g) 5x2³ x 4² =
5x(2x2) x 4x4 =
5x  4     x  16 =
   20 x 16 = 320

h) 5³  x  2² - 12 =
5x5x5 x 2x2 - 12 =
   125 x  4    - 12 =
         500   - 12 = 488